HISTORY OF HAZRAT QASIM SHEIKH AZIZAN COMPLEX BUILT BY ABDULLAH KHAN II - Babayarova Shakhnoza Shukhratovna (Scholar Express Journal, 2023)
In this article, the history of the construction of Hazrat Qasim Sheikh Azizon mosque and house built in Karmana in 1558 by Abdulla Khan ibn Iskandar Khan (1534-1598), who ruled Movarounnahr in the 16th century, and the importance of this structure for its time is shown. The article also discusses the role of Hazrat Qasim Sheikh Azizon in the socio-political and spiritual life of the state ruled by Abdullah Khan
Keywords: khanaqah; waqf; mysticism; mosque